Site-Seeing: Exploring Jesus’s Hometown - Strange, James Riley (The Biblical archaeology review, 2025)
In the early first century CE, Jesus’s hometown of Nazareth was a Galilean village like most others. With a population probably numbering only in the hundreds, it was much smaller than neighboring Yafia and was dwarfed by nearby Sepphoris, one of the Galilee’s wealthiest and most prosperous cities at the time. Nazareth today is a […]